Rootstock-Mediated Genetic Variance in Cadmium Uptake by Juvenile Cacao (Theobroma cacao L.) Genotypes, and Its Effect on Growth and Physiology - Fernández-Paz, Jessica; Cortés, Andrés J.; Hernández-Varela, Camila A.; Mejía-de-Tafur, Maria Sara; Rodriguez-Medina, Caren; Baligar, Virupax C. (Frontiers in Plant Science, 2021)
Grafting typically offers a shortcut to breed tree orchards throughout a multi-dimensional space of traits. Despite an overwhelming spectrum of rootstock-mediated effects on scion traits observed across several species, the exact nature and mechanisms underlying the rootstock-mediated effects on scion traits in cacao (Theobroma cacao L.) plants often remain overlooked. Therefore, we aimed to explicitly quantify rootstock-mediated genetic contributions in recombinant juvenile cacao plants across target traits, specifically cadmium (Cd) uptake, and its correlation with growth and physiological traits. Content of chloroplast pigments, fluorescence of chlorophyll a, leaf gas exchange, nutrient uptake and plant biomass were examined across ungrafted saplings and target rootstock×scion combinations in soils with contrasting levels of Cd. This panel considered a total of 320 progenies from open-pollinated half-sib families, and reciprocal full-sib progenies (derived from controlled crosses between the reference genotypes IMC67 and PA121). Both family types were used as rootstocks in grafts with two commercial clones (ICS95 and CCN51). A pedigree-based Best Linear Unbiased Prediction (A-BLUP) mixed model was implemented to quantify rootstock-mediated narrow-sense heritability (h2) for target traits. A Cd effect measured on rootstocks before grafting was observed on plant biomass, nutrient uptake, and content of chloroplast pigments. After grafting, damage to the Photosystem II (PSII) was also evident in some rootstock × scion combinations. Differences in the specific combining ability for Cd uptake were mostly detected in ungrafted rootstocks, or two months after grafting with the clonal CCN51 scion. Moderate rootstock effects (h2 > 0.1) were detected before grafting for five growth traits, four nutrient uptake properties, and chlorophylls and carotenoids content (h2=0.19, 95% CI 0.05-0.61, r=0.7). Such rootstock effects faded (h2 < 0.1) when rootstock genotypes were examined in soils without Cd, or four months after grafting. These results suggest a pervasive genetic conflict between the rootstock and the scion genotypes, involving the triple rootstock×scion×soil interaction when it refers to Cd and nutrient uptake, early growth, and photosynthetic process in juvenile cacao plants. Overall, deepening in these findings will harness early breeding schemes of cacao rootstock genotypes compatible with commercial clonal scions and adapted to soils enriched in toxic levels of Cd.